Multifunctional Potential of Project-Based Translation Activities of School Children who are Local Dialect Speakers (Regiolect) (Linguostylistic Studies, 2022)
The article highlights the issue of the multifunctional potential of project-based translation activities of schoolchildren who are local dialect speakers (a case study of the materials from the village of Sadzhavka, Kolomyia district, Ivano-Frankivsk region). The author analyzes how daily work on project-based translation into a foreign language influences the development of linguistic competencies (lexical, grammatical, and phonetic) of the students. Using the authentic texts of the native land and the author’s neologisms beneficially contributes to improving knowledge. The study has revealed that the project-based translation activity allows the development of such speech functions as the ability to describe and interpret the realities of native and foreign cultures, conduct intercultural-analytical studies, organize discussion and communication, and make the learning process empathic. It has been found that the main advantage of involving students in project-based translation activities is the formation of their self-motivation via well-thought-out planning and the free use and choice of research methods and techniques. It is a practically-significant aspect of young speakers’ language skills development. These activities unobtrusively promote the abilities and interests of children, motivating them for self-discovery and intercultural understanding.The research findings argue that using the project method to research the folklore heritage of the native region allows the teacher to interest students in the subject, develop their creativity, and strengthen inter-subject connections. Project-based translation activity contributes to the formation of communicative competencies of school children
Keywords: project based translation activity; ethnocultural; communicative competence; preservation of cultural heritage; self-motivation; eTwinning Plus